PERTANGGUNG JAWABAN PIDANA KORPORASIPELAKU TINDAK PIDANA KORUPSIDALAM TATA KELOLA NIAGA KOMODITAS DI INDONESIA - Saragih, Handa Yusico; Chandra, Tofik Yanuar; Paparang, Santrawan T. (SINERGI : Jurnal Riset Ilmiah, 2025)
This study examines the issue of corporate criminal liability in corruption cases occurring within the governance of Indonesia’s commodity trade sector. Corruption in this sector is marked by its complexity, often involving strategic national commodities such as mining products, plantation outputs, and state-managed funds. These offenses are frequently not committed directly by individuals but instead facilitated and executed through corporate entities that function as primary perpetrators or instruments of organized crime. Corporations, beyond being legal entities, possess internal systems capable of structuring and concealing illegal activities through collective decision-making mechanisms. The research aims to identify specific forms of corruption committed by corporations in commodity governance and to analyze how criminal liability can be applied to these legal entities. The study employs a normative juridical method with statutory, case, and conceptual approaches. It focuses on four major court decisions: the Jiwasraya case (Joko Hartono Tirto), the Asabri case (Maj. Gen. (Ret.) Adam Rachmat Damiri), the illegal tin export case (Harvey Moeis), and the illegal land acquisition case involving Surya Darmadi and Duta Palma Group. Findings reveal eight primary forms of corruption within this context: price mark-ups, manipulation of export/import quotas, falsification of production data and documents, collusion in vendor appointments using fictitious partners, concealment of illicit proceeds, illegal exports without permits, unauthorized land control, and evasion of financial obligations such as taxes, royalties, and non-tax state revenues (PNBP). Corporate liability may be established through the identification theory, vicarious liability, and strict liability principles, in line with Supreme Court Regulation No. 13 of 2016 and Article 20 of the Indonesian Penal Code (KUHP Nasional). The study concludes that criminal law enforcement must move beyond punishing individuals to targeting the corporate structures that enable systemic corruption. A structural and policy-oriented approach to corporate criminal liability is essential to ensure deterrence and promote integrity in national commodity governance